Review of Silicon Carbide Power Devices and Their Applications - Xu She; Huang, Alex Q.; Lucia, Oscar; Ozpineci, Burak (IEEE transactions on industrial electronics (1982), 2017)
Silicon carbide (SiC) power devices have been investigated extensively in the past two decades, and there are many devices commercially available now. Owing to the intrinsic material advantages of SiC over silicon (Si), SiC power devices can operate at higher voltage, higher switching frequency, and higher temperature. This paper reviews the technology progress of SiC power devices and their emerging applications. The design challenges and future trends are summarized at the end of the paper.